Beyond Compliance: The Role of Corporate Governance Strategy in Enhancing Firm Value - Ryandy; Farah Margaretha Leon; Purba, Yosephina E (Universitas Trisakti, 2024)
This study aims to examine the impact of board size, female directors, commissioner independence, majority ownership, foreign ownership, audit committee size, and firm size on the firm value. This study uses secondary data from the annual reports of non-financial companies that listed in the Indonesia Stock Exchange for the period of 2020-2023. The sample of this study used purposive sampling and obtained 54 companies as samples from 15 industrial sectors. Data analysis used to test the hypothesis is panel data regression analysis using the E-views 9 program. Based on the research results that have been obtained, it is known that the size of the board of directors and foreign ownership has a positive and significant effect on firm value. Female directors, commissioner independence, majority ownership, and company size have a negative and significant effect on firm value, while the size of the audit committee has no effect on firm value. The implication of this study is that companies in their efforts to increase firm value should pay attention to the number of directors, the number of female directors, the number of independent commissioners, and diversify shares.